Where no one has heard : the life of J. Christy Wilson, Jr. - Wilson, Ken, 1957- (William Carey Library, 2017)
"Who was J. Christy Wilson Jr.? Many have never heard his name, but Christy Wilson's life had a ripple effect in modern missions. Read the first full biography of the humble, adventurous man of prayer who helped launch the Urbana missions conference, pioneered ministry in Afghanistan when others thought it impossible, mobilized hundreds of students toward world evangelization, and reintroduced the biblical idea of leveraging one's profession for the kingdom with the term "tentmaking." Riveting, uplifting, and frequently amusing, this book will challenge you to reconsider what is possible when we dare to yield to Christ and his purposes in the world."--Publisher.